Outcomes of Different Lifestyle Approaches in a Multicentre, Open-Label, Parallel-Group, Randomised Controlled Trial of the Effectiveness of Integrating a Pragmatic Pathway for Prescribing Liraglutide 3.0 mg in Weight Management Services (STRIVE Study) - Werd Al-Najim; Babak Dehestani; Ahmed W. Al-Humadi; Danielle H. Bodicoat; Dimitris Papamargaritis; Michael Lean; Barbara McGowan; David R. Webb; John PH Wilding; Melanie J. Davies; Carel W. le Roux (Metabolites, 2025)
Background/Objectives: The STRIVE study was a multicentre, open-label, real-world clinical trial evaluating the effectiveness of a targeted prescribing pathway for liraglutide 3.0 mg as an adjunct to standard care versus standard care alone in people with obesity attending Specialist Weight Management Services (SWMS) in the UK and Ireland. This post hoc analysis focuses on the standard care arm to explore differences in outcomes between sites, particularly the potential impact of offering meal replacements as part of usual care. Methods: Participants included individuals with a BMI ≥ 35 kg/m² and at least one obesity-related complication who received standard care at five SWMS sites. All sites provided specialist nutrition and exercise counselling; however, only the Dublin site (n = 40) included meal replacements as part of routine care. Baseline characteristics and weight change data were compared between the Dublin and UK cohorts (n = 92) at 52 and 104 weeks. Statistical comparisons were made using appropriate parametric and non-parametric tests. Results: At baseline, the Dublin cohort was significantly older (p < 0.01), had a higher prevalence of hypertension (p < 0.05), and a lower reported incidence of depression/anxiety (p < 0.05) than the UK cohort. At week 52, the Dublin group achieved greater mean weight loss (−6.1%, SD ± 5.7%) compared to the UK cohort (−1.3%, SD ± 6.7%, n = 27, p < 0.01). By week 104, Dublin participants maintained a mean weight loss of −4.4% (SD ± 5.7%) while UK participants had a mean weight gain of 0.37% (SD ± 7.6%) (p < 0.05). Conclusions: The integration of meal replacements as part of usual care may have contributed to the greater and sustained weight loss observed in the Dublin cohort compared to other SWMS in the UK.